2015
DOI: 10.1139/cjm-2014-0694
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration ofBifidobacterim bifidumfor modulating microflora, acid and bile resistance, and physiological indices in mice

Abstract: Bifidobacteria are generally acknowledged as major gut microflora used as probiotics, which promote human health. In this study, the effects of the administration of Bifidobacterim bifidum on modulating gastrointestinal (GI) tract microflora, acid and bile resistance, and physiological indices in BALB/c mice were investigated. Results showed that B. bifidum can significantly improve the ecosystem of the GI tract by increasing the amount of probiotics and reducing the populations of pathogenic bacteria, as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…β-diversity analysis revealed a distinct clustering of the microbiome in the morphine analgesic group with a significant decrease in Bifidobacterium and Lactobacillus at the genus level. The dramatic depletion of Bifidobacterium and Lactobacillus, two essential and common inhabitants of the human intestine, were of particular interest because of their roles in maintaining gut homeostasis and gut epithelial integrity (32).…”
Section: Discussionmentioning
confidence: 99%
“…β-diversity analysis revealed a distinct clustering of the microbiome in the morphine analgesic group with a significant decrease in Bifidobacterium and Lactobacillus at the genus level. The dramatic depletion of Bifidobacterium and Lactobacillus, two essential and common inhabitants of the human intestine, were of particular interest because of their roles in maintaining gut homeostasis and gut epithelial integrity (32).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic strains demonstrated effectiveness in cholesterol lowering under high-cholesterol diet [19], and the role of cholesterol intake remain debatable vs. gut microbiota as a main trigger of obesity development and atherosclerosis. The mechanisms have been defined to explain the influence of gut microbiota on cholesterol metabolism [20][21][22][23][24][25][26][27][28][29][30][31]. The broad associations of liver function and development of nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH) with gut microbiota was rigorously studied [32][33][34].…”
Section: Overviewmentioning
confidence: 99%
“…An important criterion for selection of probiotic strains for development of such drugs is their ability to normalize the metabolism of lipid spectrum components, mostly cholesterol. In various experimental models of metabolic diseases and in vitro, it was shown that some strains of Lactic acid bacteria (LAB) and Bifidobacteria had effective hypocholesterolemic activity associated with enzymatic degradation of bile acids, direct binding of cholesterol by cell walls of bacteria [20][21][22][23][24][25], and changes in expression of several genes involved in lipid metabolism [20].…”
Section: Overviewmentioning
confidence: 99%
“…Oral administration of bacteria into the host is a standard protocol to study the host microbe relationship and has been utilized to understand the effect of probiotics [ 92 , 93 ] and pathogens [ 94 , 95 ] in animal models. Thus, oral administration of SRB in rodents may be used as an important tool to understand the impact of SRB and its production of H 2 S on physiological functions of the host.…”
Section: Impact Of Srb Bacterial Derived H 2 Smentioning
confidence: 99%